SECURITISATION, NATIONAL ACTION PLAN, AND LAW ON TERRORISM IN THE PHILIPPINES AND INDONESIA: QUESTIONING COMPREHENSIVE APPROACH - Anindya, Chaula Rininta Rininta (UI Scholars Hub, 2024)
The fundamental aim of the National Action Plan (NAP) on Preventing and Countering Violent Extremism (P/CVE) is to employ a comprehensive approach to addressing the root causes of violent extremism. However, does it necessarily become a real instrument to employ a comprehensive approach in P/CVE? The case of Indonesia and the Philippines will show the important factors of the people behind the policy-making process and the timing of the issuance of NAP. The NAP will only become a mere jargon of a “comprehensive approach” when there is limited access for other actors outside of the governmental agencies to be involved in the policy-making process. It will only be exploited as an instrument of securitisation because the bulk of attention is on the use of kinetic approach which is regulated under the following regulations that are issued after the NAP. In contrast, if there is a wide range of relevant actors involved, it will allow the policymakers to receive various feedback from different perspectives. Issuing NAP after the other regulations that are heavy on kinetic approach will also allow NAP to compensate for it; showing the government’s commitment to provide comprehensive security.